2016
DOI: 10.1016/j.bbrep.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Potentiating effect of glabridin from Glycyrrhiza glabra on GABA A receptors

Abstract: Extracts from Glycyrrhiza are traditionally used for the treatment of insomnia and anxiety. Glabridin is one of the main flavonoid compounds from Glycyrrhiza glabra and displays a broad range of biological properties. In the present work, we investigated the effect of glabridin on GABAA receptors. For this purpose, we employed the two-electrode voltage-clamp technique on Xenopus laevis oocytes expressing recombinant GABAA receptors. Through this approach, we observed that glabridin presents a strong potentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…It has been demonstrated the amount of GABA in the brain tissue is positively associated with the changes in sleep-wake depth ( 64 ). Furthermore, GABA serves inhibitory roles by binding to its receptor ( 65 ) and GABA A R α1 has a sedative effect ( 66 ). It has been reported that the expression of glutamate in cerebral cortex, hypothalamus and hippocampus of in PCPA-induced insomnia rats increased, while the content of 5-HT and GABA decreased compared with the control group ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated the amount of GABA in the brain tissue is positively associated with the changes in sleep-wake depth ( 64 ). Furthermore, GABA serves inhibitory roles by binding to its receptor ( 65 ) and GABA A R α1 has a sedative effect ( 66 ). It has been reported that the expression of glutamate in cerebral cortex, hypothalamus and hippocampus of in PCPA-induced insomnia rats increased, while the content of 5-HT and GABA decreased compared with the control group ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding may help us to understand the antagonistic effect of this tincture ( Herbrechter et al, 2015 ). Another flavonoid from licorice, named glabridin, was identified as a partial antagonist of the 5-HT 3A -receptor and a potentiator of GABA A -receptors ( Herbrechter et al, 2015 ; Hoffmann et al, 2016 ). The antagonistic effect of Mentha canadensis (herba) may be explained through the action of terpenes, which are known to inhibit the 5-HT 3A receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Gamma‐aminobutyric acid (GABA) is the major inhibitory neurotransmitter in the central nervous system, being GABA A receptors a target for anaesthetics and neuroleptic, anxiolytic, and anticonvulsant compounds (Simmler et al, ). G. glabra acts as a modulator of GABA A receptors (Hoffmann, Beltrán, Ziemba, Hatt, & Gisselmann, ), being able to induce sedative and anxiolytic effects. Glabridin was evaluated by examining GABA responses in acutely isolated dorsal raphe neurons of a rat (Jin et al, ).…”
Section: Pharmacological Propertiesmentioning
confidence: 99%